ORGANIC GEOCHEMICAL EVALUATION OF POTENTIAL CENOZOIC SOURCE ROCKS IN THE MOGHAN BASIN, NW IRAN: IMPLICATIONS FOR HYDROCARBON EXPLORATION. (15th June 2018) - Mirshahani, M.; Bahrami, H.; Rashidi, M.; Tarhandeh, E.; Khani, B.
Abstract : A detailed organic geochemical evaluation of potential source rock samples (n = 350) collected from outcrops and wells in the Cenozoic Moghan Basin, NW Iran, was undertaken using whole rock (Rock‐Eval pyrolysis, organic petrography) and extract (GC and GC‐MS) analyses. The studied intervals consist of Eocene to Miocene shale/sandstone successions interpreted to have been deposited in nearshore marine conditions. Three potential source rock intervals were investigated: the Salm Aghaji Formation (lower Middle Eocene), the lower member of the Ojagheshlagh Formation (upper Middle Eocene), and the Ziveh Formation (Oligo‐Miocene). The results were used to evaluate the samples' petroleum potential and thermal maturity. A range of maturity parameters indicate that these source rocks are in the early oil generation window in the study area, and outcrop samples are less mature than subsurface samples. Rock‐Eval Tmax values for the outcrop and subsurface samples range from 410–442 °C and 438–445 °C, respectively. At a regional scale, there is an eastwards increase in thermal maturity which reaches the main oil window (ca. 3000 m) in the east of the Moghan Basin, as indicated by both VRo measurements and maturity‐sensitive biomarkers. Fair to moderate TOC contents (averaging 0.72, 0.99 and 0.78 wt.%) were recorded respectively for the Salm Aghaji, Ojagheshlagh and Ziveh Formations. Average HI values of less than 200 mg HC/g TOC (131, 178 and 104 respectively for the three formations) indicate the dominance of Type III kerogen. This is consistent with detailed molecular parameters which show a dominance of C29 steranes over C27 and C28 homologues. These observations are interpreted to indicate a nearshore marine depositional environment with an abundant terrigenous organic matter input. However, HI values of several samples fall into the range of 250 to 650 mg HC/g TOC showing the local presence of Type II kerogen. Thus the geochemistry and maturity results from this study suggest that shale‐rich intervals in the Salm Aghaji, Ojagheshlagh and Ziveh Formations may be potential source rocks for the oil shows which have been recorded in wells in the Moghan Basin.